2022
DOI: 10.1021/acs.nanolett.2c02183
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened d–p Orbital Hybridization through Asymmetric Coordination Engineering of Single-Atom Catalysts for Durable Lithium–Sulfur Batteries

Abstract: Although single-atom catalysts (SACs) have been largely explored in lithium–sulfur (Li–S) batteries, the commonly reported nonpolar transition metal-N4 coordinations only demonstrate inferior adsorption and catalytic activity toward shuttled lithium polysulfides (LiPSs). Herein, single Fe atoms with asymmetric coordination configurations of Fe–N3C2–C were precisely designed and synthesized as efficient immobilizer and catalyst for LiPSs. The experimental and theoretical results elucidate that the asymmetricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…In comparison, for J-T active Mn Oh with the optimal e g occupation ( � 1) proposed by Shao-Horn and co-workers (Figure S7d), [17] the d z 2 orbital is stretched to hybridize with S 3p (Figure 1g and S16). In detail, the d z 2 orbital overlaps the 3p orbital of S near below the Fermi level and undergoes an evident peak broadening, suggesting the strong electronic coupling and efficient mutual electron transport between Mn Oh and S. [18] Meanwhile, an enlarged distance of bonding and corresponding antibonding orbitals also indicates a stable covalent Mn Oh À S bond is formed after Li 2 S 4 adsorption. [19] To conclude, accompanied with rapid electron transport between the dual-active sites in Mn Oh À OÀ Co Td backbones, the corresponding "adsorption-catalysis" process is dominated by the LiPSs adsorption competition between Co Td and Mn Oh (Figure 1j), along with the formation of covalent TMÀ S bond (Figure S17).…”
Section: Resultsmentioning
confidence: 98%
“…In comparison, for J-T active Mn Oh with the optimal e g occupation ( � 1) proposed by Shao-Horn and co-workers (Figure S7d), [17] the d z 2 orbital is stretched to hybridize with S 3p (Figure 1g and S16). In detail, the d z 2 orbital overlaps the 3p orbital of S near below the Fermi level and undergoes an evident peak broadening, suggesting the strong electronic coupling and efficient mutual electron transport between Mn Oh and S. [18] Meanwhile, an enlarged distance of bonding and corresponding antibonding orbitals also indicates a stable covalent Mn Oh À S bond is formed after Li 2 S 4 adsorption. [19] To conclude, accompanied with rapid electron transport between the dual-active sites in Mn Oh À OÀ Co Td backbones, the corresponding "adsorption-catalysis" process is dominated by the LiPSs adsorption competition between Co Td and Mn Oh (Figure 1j), along with the formation of covalent TMÀ S bond (Figure S17).…”
Section: Resultsmentioning
confidence: 98%
“…SACs always form σ and π bonds based on the d z 2 of metal with p z of sulfur and the d xz / yz of metal with p x / y of sulfur, respectively. Liu et al [80] . found that the extra π bond resulted from the hybridization between d x 2 – y 2 / xy and p orbitals through a precisely designed asymmetric coordination configuration.…”
Section: Coordination Modulation Strategiesmentioning
confidence: 99%
“…SACs always form σ and π bonds based on the d z 2 of metal with p z of sulfur and the d xz/yz of metal with p x/y of sulfur, respectively. Liu et al [80] Figure 3. a) EXAFS fitting curves of FeSAÀ PN@PNC and FeSAÀ N x @PNC.…”
Section: Non-metallic Atom Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe-N 5 -type SACs in supersaturated coordination configuration demonstrated that Fe monoatoms with high N coordination number can strengthen the immobilization of LiPSs compared to saturated coordination ( Figure 19 d) and effectively reduce the energy barriers for the conversion of LiPSs and Li 2 S nucleation ( Figure 19 e,f) [ 178 ]. In order to address the problem of insufficient adsorption capacity of M-N 4 configuration SACs for polysulfides, Fe-N 3 C 2 -C SACs constructed by using C and N as co-coordinating atoms were designed and prepared with asymmetric supersaturated coordination configurations, which not only form additional π-bonds with the p orbital hybridization of S to anchor LiPSs, but also effectively enhance the redox kinetics of LiPSs [ 179 ]. The authors demonstrated the orbital hybridization mode by calculating the predicted density of states (PDOS) of the central Fe-atoms in Fe-N 3 C 2 -C and Fe-N 4 -C after adsorption of Li 2 S ( Figure 19 g,h), which explains the strong adsorption capacity of Fe-N 3 C 2 -C for polysulfides exhibited in the UV–vis tests ( Figure 19 i).…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%